2017
DOI: 10.1093/rpd/ncx167
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Radon, Thoron and Their Progeny Concentrations in High Thoron Rural Serbia Environments

Abstract: This article deals with the variation of radon (Rn), thoron (Tn) and their progeny concentrations expressed in terms of equilibrium equivalent concentrations (EERC and EETC), in 40 houses, in four villages of Sokobanja municipality, Southern Serbia. Two types of passive detectors were used: (1) discriminative radon-thoron detector for simultaneous Rn and Tn gases measurements and (2) direct Tn and Rn progeny sensors (DRPS/DTPS) for measuring Rn and Tn progeny concentrations. Detectors were exposed simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
9
2
Order By: Relevance
“…Similar techniques were found in Indian studies [37][38][39][40][41][42][43]. Instead of CR-39, LR-115 nuclear track detectors are used in their monitors.…”
Section: Thoron Progenymentioning
confidence: 82%
See 2 more Smart Citations
“…Similar techniques were found in Indian studies [37][38][39][40][41][42][43]. Instead of CR-39, LR-115 nuclear track detectors are used in their monitors.…”
Section: Thoron Progenymentioning
confidence: 82%
“…Table 3 summarizes thoron and thoron progeny concentrations (EETC) in various countries. As can be seen from the presented data, their number is more restricted than that of radon [ 27 , 39 , 41 , 42 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Radioactivity and Resulting Dosementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, thoron progeny concentration was measured (26)(27)(28)(29)(30). The reported radon concentration ranged from a few 10 to over 100 Bq m −3 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, exposure to even low-level of thoron can result in a considerable effective dose to the respiratory tract due to the high dose conversion factor of thoron progenies compared to that of radon progenies [1,6]. Additionally, numerous surveys have revealed that the indoor levels of thoron and its progenies are comparable to, or even higher than, those of radon and its progenies in many regions [7][8][9][10][11][12][13]. Therefore, the radiological risk associated with thoron warrants significant attention.…”
Section: Introductionmentioning
confidence: 99%